Ferroelastic domain wall orientations in the (NH₄)₃H(SeO₄)₂ crystal - Pavlenko, N.; Połomska, M.; Hilczer, B. (Condensed Matter Physics, 1998)
Experimental and theoretical studies of the ferroelastic domain structure of
the (NH₄)₃H(SeO₄)₂ crystal in phases III and IV are performed. Using
the refined structural data the orientations of W - and W′-type domain
walls, as well as the temperature evolution of the domain structure are
investigated. It is shown that in spite of the fact that the room temperature
phase III has a triclinic symmetry with small deviations from monoclinic,
the domain structure in this phase differs strongly from the structure in
the case of a monoclinic symmetry which has been previously accepted in
this temperature range. In the monoclinic phase IV all the W′-type domain
walls lie almost in parallel to the (001)-plane which explains the invisibility of
W′ walls after III-IV phase transition during the observation of the domain
structure in the (001)-plane. В роботі проведено експериментальне й теоретичне вивчення доменної структури кристалу (NH₄)₃H(SeO₄)₂ у фероеластичних фазах III і IV. Використовуючи найновіші структурні дані, досліджено орієнтації доменних стінок типу W та W′. Показано, що незважаючи на
те, що при кімнатній температурі кристал має триклінну симетрію з незначними відхиленнями від моноклінної, доменна структура сильно відрізняється від тієї, яка отримується для фази з моноклінною симетрією, що було прийнято раніше для цього температурного інтервалу. У моноклінній фазі IV доменні стінки типу W′ майже паралельні
до площини (001), що пояснює факт їх зникнення при оптичних спостереженнях у цій площині.